Sumo Puff: Tidal debris or disturbed ultra-diffuse galaxy?. (26th July 2017) - Greco, Johnny P; Greene, Jenny E; Price-Whelan, Adrian M; Leauthaud, Alexie; Huang, Song; Goulding, Andy D; Strauss, Michael A; Komiyama, Yutaka; Lupton, Robert H; Miyazaki, Satoshi; Takada, Masahiro; Tanaka, Masayuki; et al.
Abstract: We report the discovery of a diffuse stellar cloud with an angular extent ≳30″, which we term "Sumo Puff", in data from the Hyper Suprime-Cam Subaru Strategic Program (HSC-SSP). While we do not have a redshift for this object, it is in close angular proximity to a post-merger galaxy at redshift z = 0.0431 and is projected within a few virial radii (assuming similar redshifts) of two other ∼ L ⋆ galaxies, which we use to bracket a potential redshift range of 0.0055 < z < 0.0431. The object's light distribution is flat, as characterized by a low Sérsic index ( n ∼ 0.3). It has a low central g -band surface brightness of ∼26.4 mag arcsec −2, large effective radius of ∼13″ (∼11 kpc at z = 0.0431 and ∼1.5 kpc at z = 0.0055), and an elongated morphology ( b / a ∼ 0.4). Its red color ( g − i ∼ 1) is consistent with a passively evolving stellar population and similar to the nearby post-merger galaxy, and we may see tidal material connecting Sumo Puff with this galaxy. We offer two possible interpretations for the nature of this object: (1) it is an extreme, galaxy-sized tidal feature associated with a recent merger event, or (2) it is a foreground dwarf galaxy with properties consistent with a quenched, disturbed, ultra-diffuse galaxy. We present a qualitative comparison with simulations that demonstrates the feasibility of forming a structure similar to this object in a merger event. Follow-up spectroscopy and/or deeper imaging to confirm the presence of the bridge of tidal material will be necessary to reveal the true nature of this object.